Dual Self‐Built Gating Boosts the Hydrogen Evolution Reaction. Issue 27 (3rd June 2022) - Zhu, Xiaohui; Wang, Chenyang; Wang, Tingli; Lan, Haihui; Ding, Yu; Shi, Hu; Liu, Lisi; Shi, Haiwen; Wang, Luyang; Wang, Huiliu; Ding, Yiran; Fu, Yingshuang; et al.
Abstract: Optimizing the intrinsic activity of active sites is an appealing strategy for accelerating the kinetics of the catalytic process. Here, a design principle, namely "dual self‐built gating", is proposed to tailor the electronic structures of catalysts. Catalytic improvement is confirmed in a model catalyst with a ReS2 –WS2 /WS2 hybridized heterostructure. As demonstrated in experimental and theoretical results, the dual gating can bidirectionally guide electron transfer and redistribute at the interface, endowing the model catalyst with an electron‐rich region. The tailored electronic structures balance the adsorption of intermediates and the desorption of hydrogen synergistically to enhance the reaction kinetics for the hydrogen evolution reaction. Interestingly, the effect of dual gating can be easily amplified by the electric field. The overpotential and Tafel slope (49 mV, 35 mV dec −1 ) obtained under the electric field for ReS2 –WS2 /WS2 catalyst with the dual self‐built gating effect are far below than those (210 mV, 116 mV dec −1 ) of the pure WS2 catalyst, which exhibits nearly four times improvement. The concept of dual gating can be applied to more systems, offering a new guideline for designing advanced electrocatalysts. Abstract : A design strategy, namely "dual self‐built gating" is reported to boost the hydrogen evolution reaction. Taking ReS2 and WS2 as an example, dual self‐built gating induces electrons from WS2 to ReS2 directionally. The tailored electronic structure can balance the adsorption of intermediates and the desorption of hydrogen synergistically, thus greatly promoting the intrinsic activity of the active sites.